Effectiveness of artificial neochordae implantation in tricuspid valve repair - Salihi, Salih; Kızıltan, Hidayet Tarık; Huraibat, Ahmad; Korkmaz, Aşkın Ali; Kara, İbrahim; Güden, Mustafa (Texas Hearth Inst, 2019)
Various techniques for treating tricuspid regurgitation have been described; however, because of scarce data about the long-term outcomes of different repairs, the optimal technique has not been established. We evaluated the effectiveness and durability of artificial neochordae implantation in the treatment of tricuspid regurgitation. From 2009 through 2014, 507 patients underwent tricuspid valve repair at our institution. Of those, 48 patients implanted with artificial neochordae were included in our study. The median age of the participants was 62 years (range, 4-77 yr) and 50% were women. Thirty patients (63%) were in New York Heart Association functional class III, and 11 (23%) were in class II. The cause of tricuspid regurgitation was functional in 33 patients (69%) and rheumatic in 15 (31%). In 46 patients, neochordae implantation was performed in addition to Kay annuloplasty (n= 13) or ring annuloplasty (n= 33). Forty-two patients were discharged from the hospital with absent or mild tricuspid regurgitation. The mean follow-up period was 44.3 +/- 20.2 months. Follow-up echocardiograms revealed that tricuspid regurgitation was absent, minimal, or mild in 38 patients (80.8%), moderate in 7, and severe in 2. Our results indicate that the use of artificial neochordae implantation as an adjunct procedure to annuloplasty leads to effective and durable repair in comparison with conventional techniques for treating tricuspid regurgitation.
WOS: 000470726100009
PubMed ID: 31236073
Keywords: Cardiac Surgical Procedures/Methods; Chordae Tendineae/Surgery; Disease-Free Survival; Heart Valve Prosthesis Implantation; Prognosis; Suture Techniques; Treatment Outcome; Tricuspid Valve/Pathology/Physiopathology; Tricuspid Valve Insufficiency/Etiology/Surgery